Controls on the abiotic exchange between aqueous sulfate and water under laboratory conditions. (14th April 2014) - Rennie, Victoria C. F.; Turchyn, Alexandra V.
<x xml:space="preserve">Abstract</x> The oxygen atoms in sulfate are known to exchange with water at low pH and at high temperature; however, it is unclear what the timescale for exchange is for the pH and temperature conditions commonly experienced in the laboratory. We present a time series of sulfate‐oxygen isotope data for solutions with two different sulfate concentrations (28 mM and 11 mM), at a range of low to intermediate pH values (1 to 5), using both hydrochloric and acetic acid. Using water enriched in 18O, we show that there is negligible exchange of oxygen atoms between sulfate and water over the course of 390 days. We use the external uncertainty in these results to calculate a lower bound estimate on the timescale for oxygen isotope exchange under these conditions. The lower bound of the timescale for oxygen isotope exchange between sulfate and water at laboratory pH is 2 × 105 hours ( 25 y), which is broadly in agreement with previous estimates. This result validates the use of δ18OSO4 as geochemical tool for a variety of solutions that are subjected to low pH at room temperature.